Keanekaragaman Serangga Pengunjung Bunga Kelapa Sawit Aksesi Kamerun Dan Angola - Siska Efendi; Dewi Rezki (Jurusan Budidaya Perkebunan, 2021)
Cameroon and Angola, accession palms oil, were two plants with different flower architectures such as bunch size, bunch length, number of spikelets and flowers, and volatile compounds produced. The difference in flower characteristics was thought to affect the presence of flower-visiting insects in the two palm oil accessions. The study aimed to determine the insects that visit Cameroon and Angola palm oil flower accessions. Insects that visit flowers were collected directly, using yellow pan traps, swing nets, and aspirators. Collected flower-visiting insects were identified as species. Diversity and evenness were calculated using the Shannon diversity index and the Simpsons’ evenness. The total number of flower-visiting insects collected was 2039 individuals. In the Angola accession, 150 individuals were found consisting of 5 orders, 10 families, and 14 species. Insects that visited Cameroon’s accession of palm oil flowers were 1889 individuals consisting of 8 orders, 16 families, and 22 species. Angola accessions’ diversity and evenness index were higher than Cameroon’s, namely 1.50; 1.14 and 1.14; 0.52. Flower-visiting insects that act as pollinators were Elaeidobius kamerunicus, Pyroderces Sp, and Thrips hawaiiensis.